The Impact of Fiscal Policy on Income Inequality in Selected Countries of Latin America - Urbanová, Anna (2017)
The region of Latin America remains the most unequal in the world, despite the downward trend of last years. The negative socioeconomic impact of high income inequality has been examined and proved by many studies. The difference between inequality rates in Latin America and more equalitarian countries is much bigger when regarding income after taxes and transfers, which follows that the source of persisting high rates of unequal income distribution might be found in ineffective fiscal policy. This thesis examines the assumed impact of implemented fiscal policy on level of income inequality for four Latin American countries (Mexico, Brazil, Chile and Colombia). In the theoretical part, theoretical background for income inequality and fiscal policy is covered. The practical part includes analysis of development of income inequality, public expenditures and tax revenues in these countries from 1992 to 2012. Subsequently, regression model proves a significant negative impact of public health expenditures on income inequality in case of Mexico, Brazil and Chile. Public spending on education is found effective in reduction of income inequality in Brazil, however in case of Chile an increase in public spending on education seems to increase unequal distribution of income among households. Main finding of this thesis is that when efficiently targeted, fiscal policies aimed at increasing expenditure on health and education systems are likely to serve as effective measures of reduction of unequal income distribution.